Practices of sustainable architectural knowledge for hospital building maintenance - Mohammad Affendy, Omardin; Liu, Yao; Diyana, Kamarudin (Global Academic Excellence, 2018)
Defect failures are the vital concern phenomena in hospital maintenance. The focusing on sustainable architectural maintenance activities for represent the knowledge practices in managing facilities of hospital. The research was to develop sustainable knowledge procedures strategies for the hospital building maintenance development. Therefore, this study is aimed to extract features contribution to the hospital building maintenance. The information is collected from several method using observations, interviews and internal document exploration. The involvement of eight of building maintenance supervisors during the data collecting. The results of the case study point out that the practices have the potential to improve the existing procedures of maintenance practices. The sustainable architectural of hospital maintenance could provide insights to the knowledge in diagnose the hospital building defects.